Marble residues in construction materials: a review of the use of marble dust in mortars, concrete and bricks - Moreno, Armando Nicolás; Ponce Palafox, César; Múzquiz Ramos, Elia Martha; Avalos Bemolte, Felipe (Revista ALCONPAT, 2022)
The objective of this work is to make a review of the results carried out using marble powder as a substitute for cement, sand, or fine aggregate in concrete, mortar, and bricks. Research carried out in various parts of the world with different experimental procedures was reviewed. It is concluded that marble powder can be used as a partial substitute for cement or fine aggregate (up to 15%, depending on the material to be replaced) without affecting the compressive strength of the samples or pieces regardless of their shape. Therefore, marble powder not only helps to reduce the pollution it generates but also to reduce its use as sand and powder, contributing to sustainable development.